2001
DOI: 10.1111/j.1365-246x.2001.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of tsunami generation and propagation from submarine slumps: the 1998 Papua New Guinea event

Abstract: SUMMAR YDeep and large submarine slumps may generate tsunamis as disastrous as tsunamis of tectonic origin. Such a landslide is likely to be the origin of the 1998 July 17 tsunami of Papua New Guinea, the deadliest tsunami in the last 50 years. Water waves devastated a 20 km stretch of coastline, wiping out three villages and killing more than 2200 people. A numerical model has been developed to study the efficiency of deep slumps in producing tsunamis and has been applied to the Papua New Guinea event.The lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 50 publications
(81 reference statements)
1
38
0
Order By: Relevance
“…Since the slide thickness (140 m at the initiation) is much smaller than the slide length in the case study, the Bingham model can be simplified by considering a single layer whose motion is initiated and driven by viscosity when the shear stress exceeds a given yield stress (Norem et al, 1991;McEwen and Malin, 1989). The resulting equations of mass and momentum conservation, written in a coordinate system linked to the topography, read (see Heinrich et al, 2001) where κ =1−ρ w /ρ s , τ xz (z=0) and τ xy (z=0) are the shear stresses at the bed surface, u = (u,v) is the depth-averaged velocity vector parallel to the bed, h is the slide thickness perpendicular to the slope, ρ w and ρ s are the water and sediments densities with a ratio ρ w /ρ s =2, θ(x,y) is the local steepest slope angle, θ x and θ y are the slope angles along xand y-axes, respectively. Values of α that deviate from unity provide information about the deviation of the slope normal profile of (u, v) from uniformity.…”
Section: Landslide Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the slide thickness (140 m at the initiation) is much smaller than the slide length in the case study, the Bingham model can be simplified by considering a single layer whose motion is initiated and driven by viscosity when the shear stress exceeds a given yield stress (Norem et al, 1991;McEwen and Malin, 1989). The resulting equations of mass and momentum conservation, written in a coordinate system linked to the topography, read (see Heinrich et al, 2001) where κ =1−ρ w /ρ s , τ xz (z=0) and τ xy (z=0) are the shear stresses at the bed surface, u = (u,v) is the depth-averaged velocity vector parallel to the bed, h is the slide thickness perpendicular to the slope, ρ w and ρ s are the water and sediments densities with a ratio ρ w /ρ s =2, θ(x,y) is the local steepest slope angle, θ x and θ y are the slope angles along xand y-axes, respectively. Values of α that deviate from unity provide information about the deviation of the slope normal profile of (u, v) from uniformity.…”
Section: Landslide Modellingmentioning
confidence: 99%
“…Equations governing the landslide and the tsunami propagation are similar and non-dispersive. They are thus solved using the same Godunov-type scheme, extended to second order by using the concept of Vanleer (Alcrudo and Garcia-Navarro, 1993; Mangeney et al, 2000), which is based on a shock-capturing method originally derived from gas dynamics models (Heinrich et al, 2001). This model is particularly adapted to deal with nonlinear waves.…”
Section: Tsunami Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…MATSUYAMA et al (1999), in a numerical simulation employing the newly obtained bathymetric data, concluded that only a low-angle reverse fault model accompanied by a large underwater landslide could explain the 1998 PNG tsunami. HEINRICH et al (2000HEINRICH et al ( , 2001 showed that a submarine landslide could closely simulate the PNG tsunami. GEIST (2000GEIST ( , 2001, OKAL and SYNOLAKIS (2001) have discussed whether earthquakes or landslides cause tsunami.…”
Section: Discussionmentioning
confidence: 99%
“…HEINRICH et al (2001) have carried out a finitedifference landslide and tsunami simulation in the near-field zone based on a shallowwater approximation. In their model, water waves were generated by sea-bottom displacements induced by a landslide.…”
Section: Seismicity and Historical Tsunamis Along The North Coast Of mentioning
confidence: 99%